تنمية الموارد البشرية من منظور تبني استراتيجية التشارك المعرفي -دراسة حالة أساتذة كلية الاقتصاد جامعة خنشلة- (Revue El-Wahat pour les Recherches et les Etudes, 2021)
This study aims to emphasize and highlight the role of knowledge management strategy in human resources development, we have been studying the case of professors of the Faculty of Economics at the University of Khenchela was studied, adopting a comprehensivesurvey sample, sixty-four questionnaires were distributed and 60 samples were analyzed, adopt spss19, and the tools of statistical analysis were represented in the coefficient of stability and honesty, arithmetic mean, standard deviation and also coefficient of variation.            The most results of the study that the Faculty of Economics at the University of Khenchela adopts the strategy of knowledge management among its employees, but does not provide a supportive environment for learning or the necessary technologies, it also neglects the importance of task forces and teamwork in creating and sharing knowledge, the study presented some recommendations, especially the reconsideration of the application of the knowledge management strategy by focusing on the various operations, without neglecting one of them as an integrated loop, and should provide the conditions that would make this strategy successful. Key words: development; human resource; strategy; knowledge management.